KEKUATAN HUKUM DAN TANGGUNG JAWAB NOTARISTERHADAP AKTA WAARMEKING - Selly Nofrianti; Raihan Putri (Indonesian Journal of Islamic and Social Science, 2024)
Waarmerking is a private deed that has previously been made and signed by the parties because the deed was made by the parties themselves without the intervention of a Notary. A deed must have legal force and certainty of date, so that to have certainty of date the parties must register the private deed at the Notary's office, namely by making the date of registration of the private deed in a special book provided by the Notary. The reality is that currently the implementation of private letters registered by a notary has many problems, many people misunderstand, private letters registered by a notary do not have a clear legal basis. Apart from that, there are also weaknesses in private letters that are registered with a Notary, where the Notary does not know the contents of the private letter and the letter is not intended to commit a particular crime. The notary only has the authority to register the letter without seeing or asking for clear information regarding the contents of the letter. This research uses normative legal research methods. Data sources come from laws and various literature such as books related to research. The research results show that the Notary's responsibility for the waarmerking deed is only limited to providing certainty of the date, namely the date of registration of the private deed in a special book. Meanwhile, regarding the legal strength of the waarmerking deed, it can provide evidentiary strength in court trials because the deed provides certainty for the judge regarding the date, identity and signature of the parties concerned.